The Therapeutic Potential of Bone Marrow Mesenchymal Stem Cells for Articular Cartilage Regeneration in Osteoarthritis - Ding, Nan; Li, Ermao; Ouyang, Xiangbin; Guo, Jin; Wei, Bo (Current Stem Cell Research & Therapy, 2021)
Osteoarthritis (OA), characterized by the degeneration and destruction of articular cartilage, is one of the most significant public health issues around the world. In the course of OA, inflammatory response is an important factor leading to cartilage destruction and exacerbation of symptoms. The low immunogenicity, multi-directional differentiation and high portability properties make bone marrow mesenchymal stem cells (BMSCs) ideal seed cells for OA. Here, we review recent literature relating to the application of BMSCs for OA cell therapy and consider the following aspects: migration and homing of BMSCs, immunomodulatory and anti-inflammatory effects of BMSCs, anti-fibrotic effects of BMSCs, the application of biological scaffolds in cartilage regeneration by BMSCs and chondrogenic differentiation of BMSCs. Injecting BMSCs into joints with an inflammatory environment may increase the risk of osteoproliferation and ectopic calcification in patients. Further evidence and studies are needed to ensure the improvement and maintenance of the intra-articular environment for cartilage repair and regeneration.
Keywords: regeneration